Requirements for storage and transport of biotechnological medical products in accordance with the regulatory framework of ministry of public health of Ukraine and detection of violations in the medical and pharmaceutical institutions - Shukaeva, O (Annals of Mechnikov’s Institute, 2020)
Introduction. The rapid development of the pharmaceutical industry and the expansion of the range of biotech drugs require special conditions to ensure the quality, storage and transport through out the entire chain: manufacturer - distributor - pharmacy - hospital - the patient.We analyzed the current legislative frame work of Ministry of Public Health of Ukraine and conducted a study to identify and analyze of typical violations in the medical and pharmaceutical institutions. The aim of the investigation was to investigate and analyze inspection acts under storage and transport of biological medical products and identify major violations during the performance requirements for storage and transportation of drugs, level of awareness about medical products which are requiring special storage requirement. Methods: systemic, logistical, structural, marketing, regulatory. Results & discussion. According to the data presented in the report «Assessing biosimilar uptake and competition in European markets» of «IMS Health», sales of medical products with biological nature - biological medicinal products and biosymilyars is about 27% of total sales of drugs in the EU. This segment of the pharmaceutical market is characterized by faster growth compared to the pharmaceutical marketas a whole. Thus, in 2012-2013 years sales of biological medical products in the EU countries increased by 5.5% compared to 1.5% increase in total sales of drugs. It is important that in Europe, according to the 2013 preparations, the market share in value terms, with eight to prepare biological products, the term of patent protection that are either already expired or will expireby 2020, and therefore they can be competitors with biosymilars. In creasing the number of medications on the market requires a careful approach of storing and preserving the quality of distribution during throughout the life of the medical products in the chain: manufacturer - distributor - pharmacy - health caresetting - patient. The percentage of major flaws in the system supply thermally labile pharmaceutical products related to violation of temperature regimes average 35 to 43%. Conclusion. Assessing the overall state of the organization, storage, transportation and complying with the requirements of "cold chain" for Ukraine should be noted that, despite some progress in this area a lot of works to be performed at all levels of health care are needed.Necessary to improve practices in the training of personnel, development of modern refrigeration equipment and means of objective control, organization of manufacturing andto provide all the equipment manufacturing for enterprises, and public health institutions and pharmacies. Need to review the functional responsibilities of pharmaceutical workers in order to strengthen the responsibility for dispensing of biotechnological medical products. Introduction The rapid development of the pharmaceutical industry and the expansion of the range of biotech drugs require special conditions to ensure the quality, storage and transport through out the entire chain: manufacturer - distributor - pharmacy - hospital - the patient.We analyzed the current legislative frame work of Ministry of Public Health of Ukraine and conducted a study to identify and analyze of typical violations in the medical and pharmaceutical institutions.The aim of the investigation was to investigate and analyze inspection acts under storage and transport of biological medical products and identify major violations during the performance requirements for storage and transportation of drugs, level of awareness about medical products which are requiring special storage requirement. Methods: systemic, logistical, structural, marketing, regulatory. Results & discussion. According to the data presented in the report «Assessing biosimilar uptakeand competition in European markets» of «IMS Health», sales of medical products with biological nature - biological medicinal products and biosymilyarsis about 27% of total sales of drugs in the EU. This segment of the pharmaceutical market is characterized by faster growth compared to the pharmaceutical marketas a whole. Thus, in 2012-2013 years sales of biological medical productsin the EU countries increased by 5.5% compared to 1.5% increase in total sales of drugs. It is important that in Europe, according to the 2013 preparations, the market share in value terms, with eight to prepare biological products, the term of patent protection that are either already expired or will expireby 2020, and therefore they can be competitors with biosymilars.In creasing the number of medications on the market requires a careful approach ofstoring and preserving the quality of distribution during throughout the life of the medical productsin the chain: manufacturer - distributor - pharmacy - health caresetting - patient. The percentage of major flaws in the system supply thermally labile pharmaceutical products related to violation of temperature regimes average 35 to 43%. Conclusion Assessing the overall state of the organization, storage, transportation and complying with the requirements of "cold chain" for Ukraine should be noted that, despite some progress in this area a lot of works to be performed at all levels of health care are needed.Necessary to improve practices in the training of personnel, development of modern refrigeration equipment and means of objective control, organization of manufacturing andto provide all the equipment manufacturing for enterprises, and public health institutions and pharmacies. Need to review the functional responsibilities of pharmaceutical workers in order to strengthen the responsibility for dispensing of biotechnological medical products.